2001
DOI: 10.1007/s002640100270
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after hip fractures in Thailand

Abstract: Hip fractures have long been considered a major threat to the survival of elderly people. Most of the studies on survival following hip fractures have been reported from developed countries where orthopedic care is well distributed. This report describes the survival experience of 330 elderly hip fracture patients who were seen at hospitals in Chiang Mai, Thailand. The mortality rate during hospitalization was 2.1%. The 3-, 6-, and 12-month survival rates after hip fractures were 91%, 88% and 83%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
25
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 13 publications
9
25
1
5
Order By: Relevance
“…When mortality was analysed in our study, 60% of patients were either overweight (body mass index BMI 26-30) or obese (BMI>30). In Thailand, it was found that male gender, old age, chronic diseases, poor ambulation before fracture and nonoperative management were associated with increased mortality [2]. In our study, increased incidence of mortality was seen in patients with nonfunctional ambulation, male gender, cardiovascular disease, and two or more comorbid conditions.…”
Section: Discussionmentioning
confidence: 49%
“…When mortality was analysed in our study, 60% of patients were either overweight (body mass index BMI 26-30) or obese (BMI>30). In Thailand, it was found that male gender, old age, chronic diseases, poor ambulation before fracture and nonoperative management were associated with increased mortality [2]. In our study, increased incidence of mortality was seen in patients with nonfunctional ambulation, male gender, cardiovascular disease, and two or more comorbid conditions.…”
Section: Discussionmentioning
confidence: 49%
“…However, the most widely reported percentage is approximately 25% [9,10]. Chariyalertsaket al reported that the 1-year mortality rate of hip fracture patients in Thailand was 17% [5]. In this study, the 1-year mortality rate of hip fracture was 9.2% (male 9.4%, Table 2 Overall mortality (cumulative number of deaths).…”
Section: Discussionmentioning
confidence: 76%
“…The mortality rate during hospitalization was 2.1%. The 3-, 6-, and 12-month survival rates after hip fractures were 91%, 88% and 83%, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…Chariyalertsak et al found that the 3-, 6-and 12-month survival rates of patients with hip fracture were 91%, 88% and 83%, respectively, and male sex, age over 80 years, presence of chronic illnesses, poor pre-fracture walking ability and nonoperative treatment proved to be significant predictors of mortality [1].…”
Section: Discussionmentioning
confidence: 99%